Bundles of Joy? Using the ERA database to explore the outcomes of CSA practice interactions - Steward, Peter R.; Rosenstock, Todd S.; Lamanna, Christine (2019)
Farmers rarely apply CSA technologies in isolation and there is a strong demand for evidence about which bundles of practices work together to enhance outcome performance. The ERA database brings together thousands of African CSA studies giving us unprecedented power to explore trade-offs when bundling a diverse suite of practices together across a diverse range of outcome indicators. We have developed a range of analytical algorithms and plotting functions to assess performance of technology bundles to be integrated as apps on the ERA website.